Biosynthesis of gold nanoparticles by Penicillium rubens and catalytic detoxification of ochratoxin A and organic dye pollutants - Bhandari, Yogesh; Varma, Sanjana; Sawant, Amol; Beemagani, Sreelatha; Jaiswal, Neha; Chaudhari, Bhushan P.; Vamkudoth, Koteswara Rao (International Microbiology, 2023)
The environmental pollution caused by chemical dyes is a growing concern nowadays. Limitations of traditional methods opened the route for nanotechnology; owing to the versatile properties of nanomaterials, gold nanoparticles (AuNPs) became a potential strategy for different applications. In the present study, biosynthesis of gold nanoparticles (BioAuNPs) was carried out by reacting chloroauric acid (HAuCl4) with cell-free filtrate of Penicillium rubens sp. nov. NCIM 1937. The AuNPs were then characterized by UV-visible spectroscopy, HR-TEM, FTIR, and DLS analysis to further examine their efficacious biosynthesis and morphological properties including size, shape, and stability. The biogenic AuNPs are polydisperse in nature, with a mean size of 14.92 +/- 5 nm. These AuNPs exhibited promising antimicrobial activity against Escherichia coli NCIM-2065, Bacillus subtilis NCIM-2010, and Penicillium verrucosum MTCC 4935. In vitro quantitative HPLC results revealed that BioAuNPs significantly inhibited the biosynthesis of ochratoxin A (OTA). Microbial fuel cells (MFCs) are intriguing for power generation and wastewater treatment since they can directly transform chemical energy stored in organic matter to electricity by extracellular electron transfer (EET) via membrane proteins. AuNPs also showed excellent potential for dye degradation of organic pollutants, viz., methylene blue (MB), phenol red (PR), bromothymol blue (BTB), Congo red (CR), and 4-nitrophenol (4-NP). All dye removal efficiencies were estimated and fitted to pseudo-first-order processes using kinetic rate constants (Ka).The present study reveals a simple, original, and eco-friendly method for the synthesis of multifunctional biogenic AuNPs that could be effective in OTA detoxification in food products and organic pollutant removal during wastewater treatment for a sustainable environment.
Keywords: Catalytic organic dye degradation; gold nanoparticles; Ochratoxin A; Penicillium rubens; Penicillium verrucosum